Subscapularis tendon tear classification and diagnosis: A systemic review and meta-analysis - Saremi, Hossein; seifrabiei, Mohamadali (Frontiers in Surgery, 2023)
Background: In current study, we performed a systematic review and meta-analysis regarding the comparison of accuracy, sensitivity and, specificity of these techniques in diagnosing SSC tendon tear. Also, we performed a systematic review on the classification of SSC tendon tear as well. Methods: English language, peer-reviewed journal publications from the first date available to March 2022 were extracted by searching the PubMed and web of science databases. Forest plot was used to graphically show the results of pooled sensitivity, specificity and accuracy of different diagnostic modalities. Results: There were six studies on using MRI for diagnosis of subscapularis tendon tear, five studies on MRI, four studies on clinical examination, one on ultrasonography and one on CT arthrography. pooled sensitivity for MRI, MRA, clinical examination, ultrasonography and CT arthrography were 0.71 (CI: 0.54; 0.87), 0.83 (0.77; 0.88), 0.49 (0.31; 0.67), 0.39 (0.29; 0.51) and 0.90 (0.72-0,97) respectively. The pooled specificity for MRI, MRA, clinical examination, ultrasonography and CT arthrography were 0.93 (CI: 0.89; 0.96), 0.86 (0.75; 0.93), 0.89 (0.73; 0.96), 0.93 (0.88; 0.96) and 0.90 (0.69;0,98) respectively. The pooled diagnostic accuracy for MRI, MRA, clinical examination, ultrasonography and CT arthrography were 0.84 (CI: 0.80; 0.88), 0.85 (0.77; 0.90), 0.76 (0.66; 0.84), 0.76 (0.70; 0.81) and 0.90 (0.78;0,96) respectively. Conclusion: According to our systematic review and meta-analysis, MR arthrography had the most accuracy in diagnosis of subscapularis tears. MR arthrography was the most sensitive and MRI and ultrasonography were the most specific in detecting subscapularis tears.